Multi Objective Optimization for Scheduling Repetitive Projects Using GA. (2016) - Mathew, Jeeno; Paul, Brijesh; Dileeplal, J.; Mathew, Tinjumol
Abstract: Projects that contain several identical or similar units are usually referred to as repetitive projects. Repetitive projects may be due to the uniform repetition of a set of activities throughout the project, or due to the physical layout of the project. Activities that repeat from one project unit to other project unit create a very important need for a project schedule that ensures the uninterrupted flow of crew from one unit to the next. This study will help to develop a method for scheduling repetitive projects with objectives of minimizing project duration, project cost and both of them with constraints of precedence relationships between activities, constraints of precedence relationships between units and constraints of the due date in which work should be complete.